Introducing the Concept of a New Pre-Referral Treatment for Severely Ill Febrile Children at Community Level : A Sociological Approach in Guinea-Bissau - Vermeersch, Audrey; Libaud-Moal, Anaëlle; Rodrigues, Amabelia; White, Nicholas J.; Olliaro, Piero; Gomes, Melba; Ashley, Elizabeth A.; Millet, Pascal (BioMed Central, 2015)
Innovative strategies are needed to tackle childhood mortality in the rural tropics. Artesunate suppositories were developed to bring emergency treatment closer to severely ill children with malaria in rural areas where injectable treatment is not possible for several hours. Adding an antibacterial rectal drug would extend this strategy to treat non-malarial febrile illness as well. The objective of these studies was to assess acceptability of such a new pre-referral strategy by healthcare providers and likely uptake by the population.